Mosque Financial Management Model: Opportunities & Obstacles (Case Study of Muhammadiyah Mosque) - Agusdiwana Suarni; Choiriah Muslimah Nurdin; Nasrullah (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2025)
Islamic Banking, Accounting & Finance International Conference 2024 (iBAF 2024) Theme: "Revolutionizing Islamic Finance, Accounting and Banking Through Artificial Intelligence (AI)" 12-13 November 2024 Editors: Dr. Amalina Mursidi, Dr Suhaila Abdul Hamid, Prof Madya Dr. Norhaziah Nawai, Prof Madya Dr. Muhamad Azrin Nazri,Dr. Mohd Adha Ibrahim